2019
DOI: 10.1186/s13071-019-3319-9
|View full text |Cite
|
Sign up to set email alerts
|

Tick burden in Bos taurus cattle and its relationship with heat stress in three agroecological zones in the tropics of Colombia

Abstract: BackgroundTicks have a negative effect on dairy and beef cattle production systems around the world, with the concomitant risk they represent for the transmission of some important infectious diseases. Colombian cattle breeds are distributed across different agroecological regions and are exposed to different environmental challenges. In humid and warmer climates such as those from the tropics, tick burden and heat stress are important factors that can compromise livestock performance. The aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Genes intervening in microorganisms or tick's immune responses in cattle have been associated with adaptive mechanisms. The expression of these genes might explain the higher tick burden in cattle with lower adabtability and higher susceptibility to experience a thermal discomfort (CA >2), as it has been observed in Colombian cattle breeds (Rocha et al, 2019). Another important associated region on BTA19 contains the regulatory associated protein of MTOR complex 1 gene (RPTOR).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Genes intervening in microorganisms or tick's immune responses in cattle have been associated with adaptive mechanisms. The expression of these genes might explain the higher tick burden in cattle with lower adabtability and higher susceptibility to experience a thermal discomfort (CA >2), as it has been observed in Colombian cattle breeds (Rocha et al, 2019). Another important associated region on BTA19 contains the regulatory associated protein of MTOR complex 1 gene (RPTOR).…”
Section: Discussionmentioning
confidence: 97%
“…The Colombian Creole cattle have been raised in a tropical environment for centuries, and they are part of conservation and genetic improvement programs, implementing pure and cross-breeding mating systems in order to maintain the genetic diversity of in vivo and in vitro germplasm banks, but also to improve the productivity of cattle populations in the country. Several Colombian cattle breeds show a better reproductive performance measured by age at first calving (AFC) and calving interval (CI) performance (Rocha et al, 2012), disease resistance and high heat tolerance (Rocha et al, 2019), attributes that make these animals an attractive genetic resource (Correal and Henao, 2000). The objective of this study was to perform a GWAS for traits that indicate adaptability such as CA, HTC, AFC and CI in the Colombian cattle breeds BON and SM, identifying genomic regions and genes associated with the phenotypic variance of these traits.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on tick burden in cattle have not evaluated the effect of live weight. Rocha et al (29) showed that in addition to age, live weight also had a significant effect on tick burden as the heavier animal have higher tick burden, and hypothesized that factors contributing to the higher tick burden in heavier animals could be either a compromised immune system in heavier older animals or that larger animals have a wider skin surface with a denser vasculature. Association between sex and tick burden on cattle suggested the role of stress due to milk production and gestation, and the implication of grazing and management strategies.…”
Section: Figure 1tick Distribution Among Body Regions Of Infested Camentioning
confidence: 99%
“…In this way, ticks can cause anemia; immunosuppression; decreased feed intake, digestion, and metabolism; reduced milk production and quality; reduced weight gain and body condition; and reduced reproduction (e.g., increasing abortion rates and lowering pregnancy rates). Infection can become significant enough to cause death in some animals [ 44 , 45 , 46 , 47 ].…”
Section: Ecology and Economic Importance Of Ticks And Tick-borne Dmentioning
confidence: 99%